Two-particle Bose–Einstein correlations in pp collisions at s√=13 TeV measured with the ATLAS detector at the LHC - Aad, G.; Abbott, B.; Abbott, D. C.; Khodinov, A.; Kostyukhin, Vadim V.; Kuchinskaya, Olesya I.; Parida, B.; Vaniachine, A. (European Physical Journal C)
This paper presents studies of Bose-Einstein correlations (BEC) in proton-proton collisions at a centre-of-mass energy of 13 TeV, using data from the ATLAS detector at the CERN Large Hadron Collider. Data were collected in a special low-luminosity configuration with a minimum-bias trigger and a high-multiplicity track trigger, accumulating integrated luminosities of 151 mu b(-1) and 8.4 nb(-1), respectively. The BEC are measured for pairs of like-sign charged particles, each with vertical bar eta vertical bar < 2.5, for two kinematic ranges: the first with particle pr > 100 MeV and the second with particle pr > 500 MeV. The BEC parameters, characterizing the source radius and particle correlation strength, are investigated as functions of charged-particle multiplicity (up to 300) and average transverse momentum of the pair (up to 1.5 GeV). The double-differential dependence on charged-particle multiplicity and average transverse momentum of the pair is also studied. The BEC radius is found to be independent of the charged-particle multiplicity for high charged-particle multiplicity (above 100), confirming a previous observation at lower energy. This saturation occurs independent of the transverse momentum of the pair.